Evaluation of community knowledge and attitude toward COVID-19: the case of Hawassa city, Sidama, Ethiopia - Birhanu Betela Warssamo (Frontiers Media S.A., 2024)
BackgroundScientific information on the knowledge and attitude of the community toward the COVID-19 pandemic is a vital step for effective control measures. This study aimed to investigate the level of knowledge and attitude of Hawassa city residents toward COVID-19 and the interaction among knowledge and attitude toward COVID-19.MethodsA community-based cross-sectional study with stratified random sampling was used from June 2020 to August 2020. Five hundred and eighty-seven residents were selected for the study, which aimed to evaluate their knowledge and attitude toward COVID-19 using a standardized structured questionnaire. Data were collected using face-to-face interviews that strictly follow the WHO and the Ministry of Health Ethiopia guidelines for COVID-19 prevention. Attitude and knowledge were categorized based on the mean score value. Descriptive statistics and two independent multiple logistic regressions were applied to identify the possible determinants of knowledge and attitude using SPSS version 20 set at 95% CIs with a value of p of <0.05 considered statistically significant.ResultsIn total, 61.7% of the participants were knowledgeable about the virus and 65.9% had a positive attitude toward COVID-19. Educational level with the categories of second degree and above (AOR = 29.709, 95% CI = 1.239-712.55), first degree (AOR = 3.476, 95% CI = 3.278-22.02), certificate/diploma (AOR = 1.062-18.24, 95% CI = 1.062-18.24), and grade 12 completed (AOR = 1.903, 95% CI = 2.12-6.809); employment status of respondents who were self-employed (AOR = 9.545, 95% CI = 1.165-78.173) and employed respondents (AOR = 10.053, 95% CI = 1.783-56.673); reading interest with categories always (AOR = 34.45, 95% CI = 26.608-4462.226) and sometimes (AOR = 17.24, 95% CI = 17.213-1661.966); and habit of using social media with categories always (AOR = 38.708, 95% CI = 5.086-294.610) and sometimes (AOR = 3.432, 95% CI = 3.504-23.378) were the significant explanatory variables that were correlated with knowledge of the respondents.ConclusionAlthough the knowledge and attitude of respondents toward COVID-19 were positive, there is a need to use more effective strategies to improve their knowledge and attitude toward COVID-19, and increasing knowledge on preventive behaviors among the community was mandatory to attain better results. The educational level, use of social media, and reading habits of the respondents appear to play significant roles in determining their level of knowledge and attitude toward COVID-19.